HUBUNGAN SELF EFFICACY DENGAN SELF CARE MENSTRUASI HYGIENE PADA REMAJA PUTRI - Kustin, Kustin; Nikmah, Juniva Namlaun (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
Self care menstrual hygiene must be done, because during menstruation the blood vessels of the uterus are more easily infected. Statistics in Indonesia in 2012 from 43.3 million adolescent girls aged 10-14 years had very poor hygiene behavior. One of the factors that cause increased self-care during menstruation is self efficacy. Self efficacy is the perception of oneself regarding how well oneself can function in certain situations. The purpose of this study was to determine the relationship between self efficacy and self care menstrual hygiene of adolescent girls. This study used a quantitative correlational type with an observational approach with a cross sectional correlation research design. The sample in this study were adolescent girls in class VII of SMPN 1 Panji, which amounted to 110 respondents using the cluster random sampling method. Univariate analysis of frequency distribution and percentage, bivariate analysis of statistical tests in this study using the Gamma test. There is a strong relationship between self efficacy and self care menstrual hygiene in adolescent girls with the results of the Gamma test obtained p value (0.000) < ? (0.05) with a value of 1.000. Researchers concluded that the majority of female students in this study had high self-efficacy in self-care menstrual hygiene. It is hoped that the school will carry out activities in the form of counseling about menstrual hygiene every year, during the student orientation period (MOS) in order to demonstrate performance that can influence hygiene management behavior during menstruation.